Measuring health inequalities: a systematic review of widely used indicators and topics - Sergi Albert-Ballestar; Anna García-Altés (BMC, 2021)
Abstract Background According to many conceptual frameworks, the first step in the monitoring cycle of health inequalities is the selection of relevant topics and indicators. However, some difficulties may arise during this selection process due to a high variety of contextual factors that may influence this step. In order to help accomplish this task successfully, a comprehensive review of the most common topics and indicators for measuring and monitoring health inequalities in countries/regions with similar socioeconomic and political status as Catalonia was performed. Methods We describe the processes and criteria used for selecting health indicators from reports, studies, and databases focusing on health inequalities. We also describe how they were grouped into well-known health topics. The topics were filtered and ranked by the number of indicators they accounted for. Results We found 691 indicators used in the study of health inequalities. The indicators were grouped into 120 topics, 34 of which were selected for having five indicators or more. Most commonly found topics in the list include "Life expectancy", "Infant mortality", "Obesity and overweight (BMI)", "Mortality rate", "Regular smokers/tobacco consumption", "Self-perceived health", "Unemployment", "Mental well-being", "Cardiovascular disease/hypertension", "Socioeconomic status (SES)/material deprivation". Conclusions A wide variety of indicators and topics for the study of health inequalities exist across different countries and organisations, although there are some clear commonalities. Reviewing the use of health indicators is a key step to know the current state of the study of health inequalities and may show how to lead the way in understanding how to overcome them.